Therapeutic Potential of Venetoclax and Selinexor in Targeting Hypoxia‐Induced Vulnerabilities in Multiple Myeloma - Seiichi Okabe; Yuya Arai; Yuko Tanaka; Akihiko Gotoh (Cancer Reports)
ABSTRACT Background Multiple myeloma (MM) is a blood cancer marked by the abnormal clonal growth of plasma cells. Hypoxia plays a critical role in the progression and treatment resistance of MM. Aims This study investigates the expression of B‐cell/CLL lymphoma 2 (BCL2) family genes. We also investigated the activity of BCL2 and exportin‐1 (XPO1) inhibitors and the potential therapeutic synergy of venetoclax and selinexor under hypoxic conditions. Methods and Results Analysis of publicly available datasets revealed hypoxia‐induced upregulation of BCL2 and BCL2‐like 11 (BCL2L11), while BCL2‐associated agonist of cell death (BAD) expression was suppressed. Venetoclax, a selective BCL2 inhibitor, demonstrated enhanced cytotoxicity and increased caspase‐3/7 activity under hypoxic conditions. Selinexor exhibited potent anti‐myeloma effects, including dose‐dependent reductions in cell viability and increased apoptotic activity. Combining selinexor with venetoclax under hypoxia produced anti‐myeloma effects, significantly reducing cell viability, increasing apoptosis, and disrupting the mitochondrial membrane potential. This combination effectively overcame resistance in bortezomib‐resistant MM cells and demonstrated efficacy in primary plasma cell leukemia (PCL) samples. Conclusion These findings highlight the potential of selinexor and venetoclax combination therapy to exploit hypoxia‐induced vulnerabilities in MM cells.